The Development of a Concept Attainment Model Based E-Worksheet to Improve the Biology Conceptual Understanding of High School Students on the Material of Echinodermata Phylum Classification - Edelia, Dewi Fortuna; Kuswanti, Nur (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Understanding concepts is an important thing to be emphasized by students so that they are able to solve problems related to the material being studied. Understanding concepts is a prerequisite to train students' thinking skills. Indicators of understanding concept include, 1) interpreting, 2) classifying, 3) comparing, 4) exemplifying, 5) explaining, 6) inferring, and 7) summarizing. Concept attainment model-based e-worksheet can be one of alternative to train understanding concepts. The purpose of this research was producing concept attainment model-based e-worksheet on the material of the Echinodermata Phylum classification which is valid, practical, and effective to improve students' conceptual understanding. This research used the 4D model, contained steps of defining, designing, developing, and disseminating. The features included in the e-worksheet are